2004
DOI: 10.1096/fj.04-2126com
|View full text |Cite
|
Sign up to set email alerts
|

Novel and therapeutic effect of caffeic acid and caffeic acid phenyl ester on hepatocarcinoma cells: complete regression of hepatoma growth and metastasis by dual mechanism

Abstract: Our previous studies have clearly shown that the angiogenic enzymes, matrix metalloproteinase (MMP) -2/9, are directly involved in human hepatic tumorigenesis and metastasis and suggest that the MMP-2/9 inhibitors, which have dual inhibitory activities on enzyme activity and transcription, represent the best candidates for achieving tumor regression. Many anti-cancer drugs have strong cellular cytotoxicity and side effects, indicating that strong anti-cancer drugs that have no or minimal cytotoxicity and side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
245
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(259 citation statements)
references
References 54 publications
9
245
0
5
Order By: Relevance
“…Previous studies have demonstrated that NF-κB is a molecular target in RCE treated cells (15,19). Our findings showed the molecular mechanism of RCE, and that RCE blocked the TPA-mediated activation of NF-κB pathway.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies have demonstrated that NF-κB is a molecular target in RCE treated cells (15,19). Our findings showed the molecular mechanism of RCE, and that RCE blocked the TPA-mediated activation of NF-κB pathway.…”
Section: Discussionsupporting
confidence: 70%
“…MMP-2, on the other hand, is usually expressed constitutively (13,14). Cytokine and 12-O-tetradecanoyl phorbol-13-acetate (TPA) treatments are capable of inducing MMP-9 expression via the activation of transcription factors such as NF-κB and activator protein-1 (AP-1) (15)(16)(17). Consequently, inhibiting MMP-9 expression and/or its upstream regulatory pathways is critical to the treatment of malignant tumors, including breast carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Downregulating or blocking tumor cell HAb18G/CD147 significantly decreased this invasive potential of HCC cells and also significantly attenuated the MMP production. MMP-2 and MMP-9 were previously reported to be involved in human hepatic tumorigenesis and metastasis (28). In this study, MMP (MMP-2 and MMP-9) gene silence in HCC cells also significantly inhibited the invasion in the coculture system, but its inhibitory effects were significantly weaker than not only HAb18G/CD147 silence in HCC cells but also MMP silence in fibroblasts.…”
Section: Discussionmentioning
confidence: 54%
“…Kang, et al [33] found that CA inhibited the activity of Fyn kinase, which belongs to the family of non-receptive proteins of tyrosine kinase, suppressing skin carcinogenesis, which suggests a chemo-preventive effect of this type of cancer. In a study performed by Chung et al [34], liver metastasis was reduced significantly, confirming the anti-tumoral and anti-metastatic effects of CA and caffeic acid phenethylester (CAPE). With respect to the antioxidant and anti-inflammatory capacity of ferulic acid, it has been observed that this acid has positive effects against Alzheimer when mice were treated with FA, reducing the activity of the coline acetyltransferase [35].…”
mentioning
confidence: 74%